NEUROEXCITATORY ACTIONS OF TAMIFLU AND ITS CARBOXYLATE METABOLITE - Izumi, Yukitoshi (2007)
Oseltamivir (Tamiflu) is now being stockpiled by several governments as a first line treatment for an anticipated outbreak of avian influenza caused by H5N1. However, abnormal behaviors and death associated with the use of Tamiflu has developed into a major issue in Japan where Tamiflu is often prescribed for seasonal influenza. Thus, it is critical to determine neuropsychiatric effects of oseltamivir and to establish methods for safe administration. Using juvenile rats and rat hippocampal slices, we investigated whether oseltamivir has adverse effects on the central nervous system. Systemic injection of oseltamivir (50mg/kg i.p.) produced no change in behavior within 2 hours. However, prior injection of oseltamivir significantly altered the duration of loss of lightning reflex following ethanol injection (3.3 g/kg, i.p.). Ethanol injection in the presence of oseltamivir also resulted in enhanced hypothermia. In the CA1 region of hippocampal slices, oseltamivir (100 μM) induced paired pulse facilitation in population spikes without changes in excitatory postsynaptic potentials. Similarly, 3 μM oseltamivir carboxylate, the active metabolite of oseltamivir, facilitated neuronal firing, though the facilitation did not involve GABAergic disinhibition. Moreover, oseltamivir carboxylate produced further facilitation following administration of 60 mM ethanol. These findings indicate that oseltamivir has effects on the central nervous system, especially when combined with other agents.